2021
DOI: 10.1186/s12964-020-00700-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-derived exosomal miR-7641 promotes breast cancer progression and metastasis

Abstract: Background Intercellular communication is crucial for breast cancer progression and metastasis. However, the role of cancer-derived exosomes and their crucial microRNA (miRNA) cargoes mediating intercellular communication requires further investigation. Methods Cancer-derived exosomes were isolated using differential centrifugation and differentially expressed miRNAs were determined by microarrays and qRT-PCR analysis. Cell proliferation, wound-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…Moreover, Wang and colleagues suggested that serum exosomal miRNA-1226-3p is a potential biomarker for diagnosing and predicting the tumor invasion or metastases of pancreatic ductal adenocarcinoma [ 16 ]. Furthermore, Shen and colleagues demonstrated that cancer-derived exosomal miR-7641 may serve as a promising noninvasive diagnostic biomarker and potential targetable candidate in breast cancer treatment [ 20 ]. We confirmed that circulating exosomal miR-101 and miR-125b panel served as a novel promising biomarker for diagnosing HCC because of its reliable ability to differentiate patients with HCC from normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Wang and colleagues suggested that serum exosomal miRNA-1226-3p is a potential biomarker for diagnosing and predicting the tumor invasion or metastases of pancreatic ductal adenocarcinoma [ 16 ]. Furthermore, Shen and colleagues demonstrated that cancer-derived exosomal miR-7641 may serve as a promising noninvasive diagnostic biomarker and potential targetable candidate in breast cancer treatment [ 20 ]. We confirmed that circulating exosomal miR-101 and miR-125b panel served as a novel promising biomarker for diagnosing HCC because of its reliable ability to differentiate patients with HCC from normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are remarkably stable in body fluids, and they can carry various contents from donor cells to recipient cells, including proteins, lipids, DNA, and RNA [ 13 , 14 ]. Emerging evidence has demonstrated that exosomes and their delivered miRNAs have potential use as novel potential biomarkers in various cancers, such as HCC [ 15 ], pancreatic ductal adenocarcinoma [ 16 ], glioblastoma [ 17 ], prostate cancer [ 18 ], colorectal cancer [ 19 ], and breast cancer [ 20 ]. However, many circulating miRNAs that have been identified as potential diagnostic biomarkers of HCC were not selected through high-throughput screening; thus, other miRNAs that may have a higher diagnostic value were ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miR-7641 levels were significantly elevated in the plasma of patients with BCA compared with patients without metastasis. Thus, miR-7641 could be considered as a promising non-invasive diagnostic biomarker [188]. In addition, the combination of four miRNAs (miR-1246 + miR-206 + miR-24 + miR-373) have been shown to have a sensitivity of 98%, specificity of 96% and accuracy of 97% for BCA detection [189].…”
Section: Exosomes In Cancer Diagnosismentioning
confidence: 99%
“…The miR-155 shuttled by exosomes introduced a novel behavior with the increased ability of cancer development and metastasis. The elevated miR-7641 in BC-derived exosomes was found in the plasma of BC patients with distant metastasis and could promote tumor growth both in vitro and in vivo 53 . MiR-7641 could promote BC-cell proliferation and invasion, and induce epigenetic modulation in recipient cells via exosome transfer.…”
Section: Tumor-derived Exosomal Components In Bc Metastasismentioning
confidence: 99%